Development of reading fluency and metacognitive knowledge of reading strategies during reciprocal teaching: do these changes actually contribute to reading comprehension? - Juhkam, Maris; Jõgi, Anna-Liisa; Soodla, Piret; Aro, Mikko (Frontiers in Psychology, 2023)
The study examined the effect of reciprocal teaching on students' reading comprehension, reading fluency, and metacognitive knowledge of reading strategies, especially among students with learning difficulties. The special focus was to assess how the increase in reading fluency and metacognitive knowledge during the intervention contributes to the reading comprehension outcome. The sample consisted of 301 Grade 3 students, of whom 77 had learning difficulties. Analyses of (co)variances were used for estimating the effects of reciprocal teaching on the development of reading comprehension, reading fluency, and metacognitive knowledge. Multigroup path analysis was used for testing the effect of increase in reading fluency and metacognitive knowledge on reading comprehension. We found reciprocal teaching had a positive effect on reading comprehension, especially for students with learning difficulties. Reading fluency and metacognitive knowledge improved significantly, but similarly in both the intervention and control groups. However, the increase in metacognitive knowledge only contributed to reading comprehension in the intervention group, not in the control group. The study sheds light on the cognitive and metacognitive mechanisms underlying students' reading comprehension process, emphasizing metacognitive knowledge and especially the systematic practice of reading strategies as key factors in improving reading comprehension.